Solitary Interdigital Condyloma Latum in a Female Adolescent: A Case Report of an Unusual Form of Secondary Syphilis - You C; Wang K; Liao M; Zhang L; He M; Ye X; Qin Y; Yang T (Dove Medical Press, 2023)
Cong You,1 Kun Wang,1 Mingyi Liao,1 Luying Zhang,1 Mintong He,1 Xiaoying Ye,1 Yongzhang Qin,2 Tao Yang1 1Department of Dermatology and Venereology; Candidate Branch of National Clinical Research Centre for Skin and Immune Diseases, The First Affiliated Hospital of Gannan Medical University, Ganzhou, People's Republic of China; 2Department of Endocrinology, The First Affiliated Hospital of Gannan Medical University, Ganzhou, People's Republic of ChinaCorrespondence: Tao Yang, Department of Dermatology and Venereology, Candidate Branch of National Clinical Research Centre for Skin and Immune Diseases, The First Affiliated Hospital of Gannan Medical University, Ganzhou, People's Republic of China, Tel +8618720732351, Email danny20021068@sina.comAbstract: Condylomata lata are flat-topped, moist papules or plaques usually found in the anogenital area as cutaneous manifestations of secondary syphilis. Here, we present a unique case of a solitary interdigital condyloma latum of secondary syphilis in a 16-year-old female sex worker without other cutaneous findings. Sexual contact history, histopathology, including direct detection of Treponema pallidum, and serological tests were essential for the diagnosis of this case. The patient reached serological cure with two doses of intramuscularly delivered penicillin G benzathine. Owing to the dramatic rise in the incidence of primary and secondary syphilis, medical workers should be aware of the atypical skin manifestations of secondary syphilis in adolescents who are at risk of acquiring sexually transmitted diseases to avoid the progression to late syphilis and further transmission to sexual partners.Keywords: interdigital condyloma latum, secondary syphilis, female adolescent